2005
DOI: 10.1079/asc42240085
|View full text |Cite
|
Sign up to set email alerts
|

Apparent ileal digestibility of amino acids in dietary ingredients for broiler chickens

Abstract: The apparent ileal digestibility coefficients of amino acids in 107 samples representing 22 food ingredients were determined using 6-week-old broiler chickens. The ingredients assayed included five cereals (barley, maize, sorghum, triticale and wheat), two cereal by-products (rice polishings and wheat middlings), four oilseed meals (canola, cottonseed, soya-bean and sunflower meals), full-fat canola, maize gluten meal, four grain legumes (chickpeas, faba beans, field peas and lupins) and five animal protein so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
156
8
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 266 publications
(199 citation statements)
references
References 60 publications
31
156
8
4
Order By: Relevance
“…The CP and crude fat contents determined for the three cultivars were within the range of 300 to 410 and 59 to 146 g/kg, respectively, reported in the literature (Gatel, 1994;Petterson et al, 1997). The amino acid profiles of the lupin cultivars are in agreement with those reported by Green and Oram (1983) and Ravindran et al (2005). White lupins were moderately good sources of lysine, but were poor in sulphur-containing amino acids, which are characteristics of grain legumes in general (Gatel, 1994).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The CP and crude fat contents determined for the three cultivars were within the range of 300 to 410 and 59 to 146 g/kg, respectively, reported in the literature (Gatel, 1994;Petterson et al, 1997). The amino acid profiles of the lupin cultivars are in agreement with those reported by Green and Oram (1983) and Ravindran et al (2005). White lupins were moderately good sources of lysine, but were poor in sulphur-containing amino acids, which are characteristics of grain legumes in general (Gatel, 1994).…”
Section: Discussionsupporting
confidence: 84%
“…No cultivar effects were observed on the AIDC of amino acids. Only one previous study has reported the ileal amino acid digestibility of white lupins for broilers (Ravindran et al, 2005). On average, the apparent ileal digestibility values determined in this study were higher than those reported by Ravindran et al (2005), which may be explained by differences in the assay methodology.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations